Gas System for the ATLAS NSW Micromegas Detectors: Design Aspects and Advanced Validation Methods for their QA/QC - Alexopoulos, T.; Gazis, E.; Maltezos, S.; Antoniou, A.; Gika, V.; Karentzos, S.; Koulouris, A.; Koutelieris, G.; Moschovakos, P. (HNPS Advances in Nuclear Physics, 2019)
In this work we present the design aspects of the Gas Distribution System of NSW Micromegas detectors, simulation results and gas flow / pressure uniformity. We also describe the appropriate gas leak test methods, a conventional and an alternative one, being used in the Quality Assurance and Quality Control of the detectors. For the performance studies we used emulated leak branches based on medical needles. We also describe proposed upgrade stages combining the proposed competitive Flow Rate Loss method with the Lock-in Amplifier technique. Further, we describe the baseline setup for the Gas Tightness Station at BB5/CERN.